The Impact Of Entrepreneurial Leadership On Organizational Crisis Management - Mezher, Ali Hamdan; Hamed, Suheir Adel (Journal of Economics and Administrative Sciences, 2020)
The current research aims to test the relationship of the entrepreneurial leadership and its factors (strategic factors, communication factors, personal factors, motivational factors) in managing the organizational crisis and its stages (detection of warning signs, readiness and prevention, containment of damages, restoration of activity, learning) among a sample of companies of the Ministry Water resources (Al-Fao State Company for the implementation of irrigation projects, Al-Rafidain Company for the implementation of dams, Iraq Company for the implementation of irrigation projects), as well as standing at the level of interest of the research companies in the search variables and their factors and stages, there is no doubt that the search variables are important to the Ministry and the company The research sample and view, given the challenges and rapid changes in the course of events, especially crisis management, entrepreneurial leadership factors, and what the search variables provide to the companies in question, the research problem was to identify the level of practice and interest, and the ability of companies to employ entrepreneurial leadership factors in crisis management, Two research hypotheses were formulated, validated by surveying the views of a class intentional class (62) views, from employees in companies and who holds the position (general manager, assistant general manager, department head, division official and unit), and the researcher employed the exploratory descriptive approach, and used The questionnaire as a key tool for gm With data and recognition at the application level and the relationship between the two research variables, the sample responses were subject to descriptive and inferential statistical analysis via two programs (AMOS V.25 & SPSS V.25). For the purpose of data processing, the researcher used statistical methods (ratios and frequencies, mean, standard deviation, The relative importance, the coefficient of relative difference, confirmatory and exploratory factor analysis, natural distribution, the simple correlation coefficient Pearson, the simple and multiple regression coefficients), and the statistical analysis has led to the availability of entrepreneurial leadership and its factors in the first order practice and interest, then the crisis management came The second order, as well as the employment of the surveyed companies to lead the leadership in strengthening the crisis management, especially through communication factors and personal factors.